PENDEKATAN VALUE FOR MONEY UNTUK PENILAIAN KINERJA TEMPAT PELELANGAN IKAN MUARA ANGKE (Value for money Approach For The Fish Auction Performance Assessment In Muara Angke) - Retno Mulinggar; Iin Solihin; Fifi Dwi Resti (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2012)
ABSTRACTFish Auction Place known as Tempat Pelelangan Ikan (TPI) is one of the public facilities where its functions have to serve the community on fish marketing in the fishing port. The daily auction activities in TPI Muara Angke include weighing, recording and auctioning. It is necessary to measure the performance of TPI Muara Angke to determine TPI Muara Angke perform with its functions and roles. The objectives of this research were measuring the performance level of TPI activity in terms of economy, efficiency and effectiveness of TPI Muara Angke with the Value for money (VFM) approach. The results showed that the performance in TPI Muara Angke PPI is sufficient economical (87.61%), inefficient (121.83%) and ineffective (81.69%).Keywords: performance, fish auction place, value for money------ABSTRAKTempat Pelelangan Ikan (TPI) merupakan salah satu fasilitas publik yang berfungsi melayani masyarakat dalam pemasaran hasil tangkapan di pelabuhan perikanan. Aktivitas pelelangan di TPI Muara Angke dilakukan setiap hari meliputi